Kontrowersje wokół wykładni prawa – studium przypadku - Duniewska, Zofia (Studia Prawa Publicznego, 2022)
The interpretation of the law plays a speciﬁc role in the whole legal system. In the vast area of constantly changing provisions of administrative law, with all their numerous imperfections, this interpretation takes on particular importance. An interpretative decision may be a simple reﬂection of a provision’s content, or it may take a slightly different form determined as a result of decoding it in the process of interpretation. The interpreter of the law must be guided by the requirements of the law, and achievements of the general theory of law, it must be based on rational grounds that allow for a reasonable and fair balance of arguments that are important in each case. It is primarily the letter of the law, the place of regulation in the legal system and the functions and purposes assigned to the interpreted provisions that determine the result of the interpretation. In the process of applying the law, this result determines the content of a decision taken. It has a signiﬁcant inﬂuence on the position of the individual bound by such a decision, also in situations where this decision may cause justiﬁable apprehensions about its fairness. The interpretation of the law ordinarily focuses on resolving doubts against the background of speciﬁc cases under consideration. The article presents such a situation. I describe controversies relating to the interpretation of one of the provisions formulating the conditions that must be met by a person applying for the title of professor. In this case, it is a matter of the conditions for achievements obtained by her in training academic staff. The assumption that these conditions had not been cumulatively met affected a decision of the Central Commission for Degrees and Titles to refuse the presentation of the candidate to the President of the Republic of Poland for conferral of this title. But is there always a legal justiﬁcation for challenging the fulﬁlment of these conditions? I will try to answer this question in this paper.